Social Psychological Perspectives on Trump Supporters - Thomas F. Pettigrew (Journal of Social and Political Psychology, 2017)
No one factor describes Trump’s supporters. But an array of factors – many of them reflecting five major social psychological phenomena can help to account for this extraordinary political event: authoritarianism, social dominance orientation, prejudice, relative deprivation, and intergroup contact. Research on the topic demonstrates that these theories and concepts of social psychology prove centrally important in helping to understand this unexpected event. This paper describes the supporting data for this statement and demonstrates the close parallels between these American results and those of research on far-right European supporters.